Analysis of relapse childhood acute lymphoblastic leukemia at Hue Cenntral Hospital in Vietnam - Hoa, Nguyen Thi Kim; Hao, Tran Kiem; Ha, Chau Van; Watanabe, Kazuyo (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.